The Development of Chinese Nuclear Forces: Start of a Deep Transformation - V. B. Kashin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
China is currently the only member of the UN Security Council that is actively increasing the quality and quantity of its nuclear potential. Exactly how far China is willing to go in developing its nuclear forces remains a subject of discussion. The prevailing view is that China is seeking to implement a limited increase in its nuclear arsenal in order to secure the potential for a guaranteed re taliation in the face of the US continuously improving its missile defense systems. Since late 1990s, the development of air and naval forces of the Chinese People’s Liberation Army (PLA) has been a subject of increased attention both in Asia and in the world at large. Nuclear potential was not perceived as a priority for China’s development of its military power and remained in the background. However, the events of recent years have shown that the world does not quite realize the true scale of China’s efforts in creating strategic nuclear forces. At this point, it can be perceived as a fait accompli that China has managed to implement most of its long-term program for the modernization of its nuclear forces without attracting too much attention from other major countries and, above all, from the world’s sole superpower.